Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Biology in Space and Life on Earth 2007
DOI: 10.1002/9783527617005.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Adherent Cells in Microgravity

Abstract: re , and Betty V. Nusgens Why Cell Biology Research in Microgravity?It is obvious that a journey in an orbiting spacecraft induces in most astronauts (cosmonauts) a signifi cant reduction of bone mass. This is accompanied by a large redistribution of the body fl uids and oedema of the upper part of the body and various disorders of the vascular system by alteration of the balance of the body fl uids. Altered renal function and bone resorption were suggested to be responsible for an increased propensity in form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 177 publications
0
3
0
Order By: Relevance
“…The most likely candidates to assume the role of these structures are various elements of the cytoskeleton, the nucleus, intracellular organelles, and also certain cell surface receptors (integrins), which interact both with cytoskeletal structures and the extracellular matrix. These structures are able to sense constraints and deformations in the matrix which are caused either by a gravitational or mechanical field and convert this signal into intracellular messengers, which then give rise to a cellular response to the changes in gravity [ 21 , 27 ]. It is also noteworthy that the cytoskeleton and integrins are not the primary sensors but react in response to their regulatory proteins (controllers of polymerization/destabilization agent).…”
Section: Mechanotransductors As Gravity Sensorsmentioning
confidence: 99%
“…The most likely candidates to assume the role of these structures are various elements of the cytoskeleton, the nucleus, intracellular organelles, and also certain cell surface receptors (integrins), which interact both with cytoskeletal structures and the extracellular matrix. These structures are able to sense constraints and deformations in the matrix which are caused either by a gravitational or mechanical field and convert this signal into intracellular messengers, which then give rise to a cellular response to the changes in gravity [ 21 , 27 ]. It is also noteworthy that the cytoskeleton and integrins are not the primary sensors but react in response to their regulatory proteins (controllers of polymerization/destabilization agent).…”
Section: Mechanotransductors As Gravity Sensorsmentioning
confidence: 99%
“…Both micro-and hyper-gravity was shown to affect various cellular processes such as gene expression [304,305], proliferation [306], differentiation [307][308][309][310][311][312], autophagy [310,313,314] and cell death [305,310,315]. Although the mechanism of cellular graviperception remains unclear [316,317], previous studies suggested an essential role of the cytoskeleton [305], adhesive molecules [318], and cell membrane mechanoreceptors in that process. It is known that the reorganization of cytoskeletal fibers caused by mechanical forces such as altered gravity strongly alters cell functioning [294,319,320].…”
Section: Gravitational Forces Affecting Biomembranesmentioning
confidence: 99%
“…There is still a considerable uncertainty in regard to the establishment of the exact mechanism of the cellular graviperception (Lambert et al 2007;Sundaresan et al 2004). However, a substantial amount of literature indicates the vital role of the cellular cytoskeleton (Xu et al 2018), along with mechanoreceptors and adhesive molecules (Rudimov and Buravkova 2016) in those processes.…”
Section: Introductionmentioning
confidence: 99%